Detection of atrial fibrillation and other abnormal rhythms from ECG using a multi-layer classifier architecture. (3rd June 2019) - Mukherjee, Ayan; Dutta Choudhury, Anirban; Datta, Shreyasi; Puri, Chetanya; Banerjee, Rohan; Singh, Rituraj; Ukil, Arijit; Bandyopadhyay, Soma; Pal, Arpan; Khandelwal, Sundeep
Abstract: Objective : Atrial fibrillation (AF) and other types of abnormal heart rhythm are related to multiple fatal cardiovascular diseases that affect the quality of human life. Hence the development of an automated robust method that can reliably detect AF, in addition to other non-sinus and sinus rhythms, would be a valuable addition to medicine. The present study focuses on developing an algorithm for the classification of short, single-lead electrocardiogram (ECG) recordings into normal, AF, other abnormal rhythms and noisy classes. Approach : The proposed classification framework presents a two-layer, three-node architecture comprising binary classifiers. PQRST markers are detected on each ECG recording, followed by noise removal using a spectrogram power based novel adaptive thresholding scheme. Next, a feature pool comprising time, frequency, morphological and statistical domain ECG features is extracted for the classification task. At each node of the classification framework, suitable feature subsets, identified through feature ranking and dimension reduction, are selected for use. Adaptive boosting is selected as the classifier for the present case. The training data comprises 8528 ECG recordings provided under the PhysioNet 2017 Challenge. F1 scores averaged across the three non-noisy classes are taken as the performance metric. Main result : The final five-fold cross-validation score achieved by the proposed framework on the training data has high accuracy with low variance (0.8254 0.0043). Significance : Further, the proposed algorithm has achieved joint first place in the PhysioNet/Computing in Cardiology Challenge 2017 with a score of 0.83 computed on a hidden test dataset.